2013
DOI: 10.1371/journal.pone.0064337
|View full text |Cite
|
Sign up to set email alerts
|

The Small Molecule Triclabendazole Decreases the Intracellular Level of Cyclic AMP and Increases Resistance to Stress in Saccharomyces cerevisiae

Abstract: The Ras-adenylyl cyclase-protein kinase A nutrient-sensing pathway controls metabolism, proliferation and resistance to stress in Saccharomyces cerevisiae. The genetic disruption of this pathway increases resistance to a variety of stresses. We show here that the pharmacological inhibition of this pathway by the drug triclabendazole increases resistance to oxidants, heat stress and extends the chronological life. Evidence is presented that triclabendazole decreases the intracellular level of cyclic AMP by inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 51 publications
(51 reference statements)
2
6
0
Order By: Relevance
“…Recently, TCBZ was reported to inhibit adenylate cyclase activity in yeast and/or inhibit the association of GTP-Ras with adenylate cyclase [47]. Interestingly, F. hepatica has one of the most active adenylate cyclase activities in biology and this activity is associated with the parasite's membrane fraction [48].…”
Section: Biochemistry Of Tcbz Actionmentioning
confidence: 99%
“…Recently, TCBZ was reported to inhibit adenylate cyclase activity in yeast and/or inhibit the association of GTP-Ras with adenylate cyclase [47]. Interestingly, F. hepatica has one of the most active adenylate cyclase activities in biology and this activity is associated with the parasite's membrane fraction [48].…”
Section: Biochemistry Of Tcbz Actionmentioning
confidence: 99%
“…Recently it was reported that TCBZ can inhibit adenylate cyclase (AC) activity in yeast [ 32 ], but despite being widely studied in F. hepatica [ 80 ], there are still no in vitro studies of AC variation in response to drug administration. To gain insight into this possible mechanism, we investigated if AC expression was skewed in our samples.…”
Section: Resultsmentioning
confidence: 99%
“…The role of microtubules in TCBZ pathogenesis was further suggested by several lines of evidence, like the detection of cell division inhibition in vitelline and reproductive cells [ 27 29 ], the reduction in the transport of tegumental secretory bodies [ 22 ], and the inhibition of tubulin immunostaining [ 30 , 31 ]. Surprisingly, TCBZ was recently reported to inhibit adenylate cyclase activity in yeast, activating the stress response [ 32 ]. This effect has not been observed in the liver fluke so far, but considering the role of cAMP as second messenger, it might provide an explanation for the pleiotropic effects of the drug.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the studies on the mechanism of action of TCBZ have been carried out with TCBZ.SO. The precise mechanism remains to be fully elucidated, but there is more evidence for an action against microtubules and microtubule-based processes than for other possibilities, such as against energy metabolism or neuromuscular co-ordination [28].…”
Section: Mechanism Of Action Of Triclabendazolementioning
confidence: 99%